(untitled) (Bangladesh Journal of Medical Biochemistry, 2017)
Egg is an easily available, inexpensive and a major source of proteins, fats, vitamins and minerals, but its cholesterol content is high (about 200 mg per egg) and it is frequently blamed for atherosclerosis with consequent cardiovascular diseases. Eggs are very popular to young people and parents are always concerned with their daily consumption. The aim of the study was to evaluate the effect of consumption of eggs on serum lipid profile of healthy young adults. It was a prospective comparative study carried out in the Department of Biochemistry, Sylhet MAG Osmani Medical College, during the period from January to December, 2014. Eighty (80) non-diabetic, normotensive healthy young adults of 18-30 years of age were enrolled as study population. Among them 40 randomly selected subjects consumed one egg/day (Intervention group) and 40 subjects did not consume egg for 4 weeks’ study period (Control group). Baseline BMI, BP, fasting blood glucose and lipid profile were estimated. After 4 weeks, lipid profile was estimated in each group. Informed written consent was taken from each participant. Permission was taken from Ethical Committee of the Institute. Data were analyzed by SPSS. Chi-square test, unpaired and paired ’t’ test were done. In the intervention group, serum total cholesterol (TC) and LDL cholesterol (LDL-C) significantly decreased at the end of 4th week, but serum HDL cholesterol (HDL-C) and serum triglyceride (TG) did not differ significantly from baseline. In control group, serum HDL-C significantly decreased at the end of 4th week but serum TC, LDL-C and TG did not differ significantly. It may be concluded that daily consumption of one egg does not unfavorably influence on lipid profile in young adults. Further studies with larger sample size with and without risk factors may be conducted on middle and old age subjects. Bangladesh J Med Biochem 2015; 8(1): 05-09